A Comparison Of The Recognition Of Islamic And Christian Counselling In Malaysia - ZAKARIA, NORAZLINA (2017)
This thesis is a research in the field of comparative religion studies, which compares Islam and Christianity, focuses on counselling as a comparative subject and the recognition issue as the domain of the research. This study is conducted due to several research problems, which are the imprecise definition of Islamic and Christian counselling, lack of contemporary report on Islamic and Christian counselling in Malaysia, the recognition issues on the practice of Islamic and Christian counselling, the ignorance of similarities and differences between Islamic and Christian counselling and the precariousness in the practice of Islamic counselling compared to Christian counselling.